WAKF: A Will of Allah in Quran for Fraternity, Humanity and Charity: Promoting Unity, Altruism, and Social Welfare through Wakf (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Wakf is a one of a kind, unblemished, conspicuously social, legitimate and financial Islamic Institution. Wakf, truly implies commitment or detainment. Each Wakf must have certain items .These articles can be legitimate, invalid, incompletely substantial and halfway invalid. Wakf can be Public or Private. There are such a large number of items and approaches to serve network and society. The scientist needs to restore the real reason for making wakf and not simply to assuage one's own spirit and something done to demonstrate the general public being a religious and devout individual. Wakf is the best approach to devote one's property to serve humankind and to do the welfare deeds.But the incongruity of the Muslim people group is that their forthcoming age isn't much mindful about the objects of the wakf.The scientist needs to advance through this article all should meet up to advance crew, mankind and philanthropy.